Confronting the challenges of urban development in Sao Paulo: the operacoes interligadas/urbanas - Hewitt, W.E. (Ted) (2001)
This article examines the contribution of international municipal cooperation (IMC) to the resolution of long standing planning challenges in the city of Sao Paulo (Brazil), South America's largest urban agglomeration. Specifically, the study investigates the early development and subsequent evolution of a planning-related project developed in collaboration with the city of Toronto, Canada. In its first phase-dubbed the Operacoes Interligadas (OI) - the initiative was directed towards expansion and improvement of Sao Paulo's housing stock. The second phase, known as the Operacoes Urbanas, has focused more broadly on urban renewal. As will be shown, both phases of the programme have provided an important fund-raising mechanism for confronting the challenges of urban growth and change. At the same time, however, the study reveals a number of limitations to the overall strategy, perhaps restricting its use as a model for other developing world cities. - Reproduced
Keywords: Urban development